2002
DOI: 10.2310/6650.2002.33517
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-α Mediates Cigarette Smoke Extract- and Complement Factor 5a-Stimulated Interleukin-8 Release in Human Bronchial Epithelial Cells

Abstract: Collectively, these data suggest that PKC activators in addition to CSE augment C5a-stimulated IL-8 release from HBEC and that CSE and C5a stimulate IL-8 release in HBEC by activating the calcium-dependent PKCalpha isoform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
14
2
Order By: Relevance
“…Clearly, this isoenzyme plays many roles in airway epithelial signaling depending on the specific cell type and stimulatory agent involved. Adding to this complexity is the observation that interleukin release can be mediated by other PKC isoforms, such as the stimulation of cigarette smoke-induced IL-8 release via PKC␣ (11). Due to the nature of auto-downregulation in response to activation of PKC, it is not surprising that multiple PKC isoforms would demonstrate overlapping functions.…”
Section: Discussionmentioning
confidence: 96%
“…Clearly, this isoenzyme plays many roles in airway epithelial signaling depending on the specific cell type and stimulatory agent involved. Adding to this complexity is the observation that interleukin release can be mediated by other PKC isoforms, such as the stimulation of cigarette smoke-induced IL-8 release via PKC␣ (11). Due to the nature of auto-downregulation in response to activation of PKC, it is not surprising that multiple PKC isoforms would demonstrate overlapping functions.…”
Section: Discussionmentioning
confidence: 96%
“…PKC family members are activated in response to mitogens, inflammatory stimuli and stress and play important roles in a variety of cellular functions including cell metabolisms, gene expression, mitogenesis, proliferation, differentiation, tumor promotion and apoptosis (Brodie and Blumberg, 2003;Jackson and Foster, 2004;Yoshida et al, 2002). Accumulating reports have indicated that protein kinase Cs (PKCs) contribute to IL-8 production in a variety of cells (Kashyap et al, 2002;Wyatt et al, 2001). Recent studies supported that PKCδ, one of the novel PKCs, mediates up-regulation of inflammationrelated proteins such as TNF-α, IL-1β, IL-8, and ICAM-1 in epithelial cells, endothelial cells, and monocytes (Kontny et al, 2000;Rahman et al, 2001;Vallee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to inhibit ERK, c-src tyrosine kinase, and protein kinase C pathways because of their involvement in MMP expression (21)(22)(23). Northern blot analysis showed that 24-h treatment with 5% CSE alone increased MMP-1 mRNA in SAECs (Fig.…”
Section: Cse Increases Mmp-1 In Airway Epithelialmentioning
confidence: 99%